2019
DOI: 10.1111/tpj.14537
|View full text |Cite
|
Sign up to set email alerts
|

A unique chromosome translocation disrupting ClWIP1 leads to gynoecy in watermelon

Abstract: Summary To understand sex determination in watermelon (Citrullus lanatus), a spontaneous gynoecious watermelon mutant, XHBGM, was selected from the monoecious wild type XHB. Using map‐based cloning, resequencing and fluorescence in situ hybridization analysis, a unique chromosome translocation between chromosome 2 and chromosome 3 was found in XHBGM. Based on the breakpoint location in chromosome 2, a putative C2H2 zinc finger transcription factor gene, ClWIP1 (gene ID Cla008537), an orthologue of the melon gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 60 publications
1
34
0
Order By: Relevance
“…Studies have indicated that CsWIP1 can directly bind to the promoter of CsACO2 and inhibit its expression in cucumber plants, which affects the parthenocarpic composition [35]. Similar mechanisms have been observed in melons [34] and watermelons [36]. In the present study, the WIP transcription factor CSA026801 was also identified in DEGs.…”
Section: Role Of Ethylene-related Genes In Flower Formation In Pistilsupporting
confidence: 84%
See 1 more Smart Citation
“…Studies have indicated that CsWIP1 can directly bind to the promoter of CsACO2 and inhibit its expression in cucumber plants, which affects the parthenocarpic composition [35]. Similar mechanisms have been observed in melons [34] and watermelons [36]. In the present study, the WIP transcription factor CSA026801 was also identified in DEGs.…”
Section: Role Of Ethylene-related Genes In Flower Formation In Pistilsupporting
confidence: 84%
“…Furthermore, a loss-of-function mutation in the CmWIP1 gene induces the formation of gynoecious plants [34]. The ortholog CsWIP1 of CmWIP1 can bind to the promoter of CsACO2 and suppress its expression, thereby regulating the development of unisexual flowers in cucumbers [35]; ClWIP1 was determined to be involved in the sex determination of watermelons [36].…”
Section: Introductionmentioning
confidence: 99%
“…In gynoecious lines, an insertion of a transposon (1.3 kb downstream of the gene) represses the expression of CmWIP1 via epigenetic changes in its gene promoter. In watermelon, a chromosome translocation produced an insertion mutation in the ClWIP1 gene (the CmWIP1 ortholog), leading to a gynoecious line (Zhang et al, 2019). Natural mutants of CsWIP1 in cucumber varieties are unavailable.…”
Section: Genes Resulting In Pistillate Primordia Initiationmentioning
confidence: 99%
“…Therefore, phenotype–genotype relationships are proposed as: monoecious, AAGyGyTmTm ; trimonoecious, AAGyGytmtm ; andromonoecious, aaGyGy ; gynoecious, AAgygyTmTm ; gynomonoecious, AAgygytmtm ; and hermaphroditic, aagygy . Recent gene cloning helped to identify that the a gene is a mutation in ClACS7 / CitACS4 , and the gy gene is mutated in ClWIP1 , which are orthologous genes of CsACS2 / CmACS7 and CsWIP1 / CmWIP1 , respectively (Boualem et al, 2016; Ji et al, 2016; Manzano et al, 2016;Zhang et al, 2019). Therefore, it seems that the WIP1 - CsACS2 / CmACS7 relationship is conserved in all the studied cucurbits.…”
Section: Gene Interaction Conferring Sex Expressionmentioning
confidence: 99%
“…Cucumber has a unique system for gynoecious sex expression which is based on CNV of a 30.2 kb region containing CsACS1G, a duplicated copy of CsACS1 but with recombinant promoter 38,39 . In melon and watermelon, the gynoecious sex expression is controlled by WIP1 homologs encoding a C2H2 zinc-finger transcription factor, which is a negative regulator of femaleness 66,67 . No gynoecious WIP1 mutant (CsWIP1) have been identified in natural cucumber populations.…”
Section: Structure and Function Of The F Locus In Cucumbermentioning
confidence: 99%